TETRALOGI FALLOT DAN ATRESIA PULMONAL - Supit, Alice I.; Kaunang, Erling D. (Jurnal Biomedik : JBM, 2012)
Abstract: Congenital heart disease is a structural defect due to the malformation of the heart, aorta, and or great blood vessels. It is the most frequent congenital malformation in newborn babies. Tetralogy of Fallot is one of the congenital heart diseases (CHD) with central cyanosis, and covers 5-10% of all CHD. We reported a boy of one year old with Tetralogy of Fallot and pulmonal atresia (ToF-PA), associated with bronchopneumonia. The diagnosis was based on anamnesis, physical examination, and other supporting examinations. The chest X-ray showed a normal sized heart (CTR 57%) with coer-en-sabot shape, and right and left parahilar infiltration, which resulted in bronchopneumonia and ToF. The electrocardiography showed a right deviation of axis and a hypertrophy of the right ventricle; the echocardiography showed a right ventricle hypertrophy, an over-riding aorta, a large malalignment of the ventricular septal defect, no visualization of pulmonar artery, and no visualization of patent ductus arteriosus (PDA). Conclusion: Based on all the tests performed, the diagnosis of this patient was Tetralogy of Fallot and pulmonal atresia (ToF-PA), associated with bronchopneumonia. The prognosis related to bronchopneumonia in this case was good due to the use of antibiotics. Keywords: tetralogy of Fallot, pulmona atresia, bronchopneumonia.Â Â Abstrak: Penyakit jantung bawaan (PJB) ialah kelainan struktural akibat malformasi jantung, aorta dan atau pembuluh darah besar, dan merupakan kelainan kongenital tersering pada bayi baru lahir. Tetralogi Fallot merupakan salah satu PJB dengan sianosis sentral, dan mencakup 5-10% dari seluruh PJB. Kami melaporkan kasus seorang anak laki-laki berusia satu tahun dengan Tetralogi Fallot dan atresia pulmonal (ToF-PA) disertai bronkopneumonia. Diagnosis ditegakkan melalui anamnesis, pemeriksaan fisik, dan pemeriksaan penunjang. Hasil ekspertisi foto toraks AP memperlihatkan ukuran jantung normal (CTR 57%) berbentuk coer-en-sabot, dan pada paru-paru terlihat infiltrat parahilar kanan dan kiri serta corakan vaskular paru berkurang yang menunjukkan suspek bronkopneumonia dan ToF. Elektrokardiografi memperlihatkan deviasi aksis ke kanan dan hipertrofi ventrikel kanan, dan pada ekokardiografi tampak right ventricle hypertrophy, overriding aorta, VSD malalignment besar, tidak tampak visualisasi arteri pulmonal, dan tidak tampak patent ductus arteriosus (PDA) dengan hasil Tetralogi Fallot dan atresia pulmonal. Simpulan: Berdasarkan hasil pemeriksaan yang dilakukan, diagnosis pasien ini ialah Tetralogi Fallot dan atresia pulmonal (ToF-PA) disertai bronkopneumonia. Prognosis bronkopenumonia pada kasus ini baik yang dapat diatasi dengan antibiotika.Kata kunci: tetralogi Fallot, atresia pulmonal, bronkopneumonia. Â